Five Decades of Occupation in the Light of Centennial Lithuanian Law Development - Maksimaitis, Mindaugas (Teisė, 2019)
[full article and abstract in Lithuanian; abstract in English]The article attempts to summarize the results of losses and achievements of soviet Lithuanian law science development and discuss its remaining significance.
Keywords: law history science; academical freedom; socialistic law; Soviet law